Outcome of invasive mechanical ventilation after pediatric allogeneic hematopoietic SCT: results from a prospective, multicenter registry - van Gestel, J P J; Bierings, M B; Dauger, S; Dalle, J-H; Pavlíček, P; Sedláček, P; Monteiro, L M; Lankester, A; Bollen, C W (Bone marrow transplantation, 2014)
Exact data on prognosis of children receiving invasive mechanical ventilation (IMV) after allogeneic hematopoietic SCT (HSCT) is lacking. We therefore started a prospective registry in four European university HSCT centers (Leiden, Paris, Prague and Utrecht) and their pediatric intensive care units (PICUs). The registry started in January 2009. In January 2013, the four centers together had treated a total of 83 admissions with IMV. The case fatality rate in these patients was 52%. Mortality 6 months after PICU discharge was 45%. There were significant differences between centers in the proportion of children who received IMV after HSCT (6-23%, P<0.01), in severity of disease on admission to PICU (predicted mortality 14-37%, P<0.01), in applying noninvasive ventilation before IMV (3-75% of admissions, P<0.01) and in the use of renal replacement therapy (RRT) (8-58% of admissions, P<0.01). Severe impairment in oxygenation, use of RRT and CMV viremia were independent predictors of mortality. Our study shows that mortality in children receiving IMV after HSCT remains high, but has clearly improved compared with older studies. Patient selection and treatment in PICU differed significantly between centers, which underscores the need to standardize and optimize the PICU admission criteria, ventilatory strategies and therapies applied in PICU.
Keywords: výsledek terapie; Respiration, Artificial; Male; Child, Preschool; Risk Factors; Adolescent; Transplantation, Homologous; prognóza; Infant; Child; dítě; transplantace hematopoetických kmenových buněk; Prospective Studies; umělé dýchání; mužské pohlaví; příprava pacienta k transplantaci; mladiství; Treatment Outcome; homologní transplantace; předškolní dítě; Transplantation Conditioning; lidé; ženské pohlaví; Humans; kojenec; rizikové faktory; Prognosis; Female; Hematopoietic Stem Cell Transplantation; prospektivní studie